IMPLEMENTASI HAK-HAK TERSANGKA SEBAGAI PERWUJUDAN ASAS PRADUGA TIDAK BERSALAH DALAM PROSES PEMERIKSAAN DI TINGKAT PENYIDIKAN (STUDI KASUS DI POLRESTA KOTA PEKANBARU) (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
At the level of implementation, the right of suspects to be immediately investigated by investigators is slow and some are fast. It really depends on the type of case being investigated (mild, moderate, severe) and the availability of investigators to conduct an investigation. Besides that, the readiness of the facilities and infrastructure of the investigation also affects the smoothness of the investigation process, thus affecting the rights of the suspect to get an immediate examination from the investigator.This study uses a sociological juridical research method. This research was conducted at Pekanbaru City Police by taking data through interviews with the Pekanbaru City Police Criminal Investigation Unit and Pekanbaru City Police Criminal Investigation Unit. Also as additional data, the author distributed questionnaires to 50 suspects and detainees. The collected data is analyzed qualitatively and deductive conclusions are drawn, that is, drawing conclusions from general to specific.The results of this study indicate that: First, the implementation of the protection of the rights of suspects in the examination process by investigators in the jurisdiction of the Pekanbaru Resort Police has not been optimally carried out based on the Application of the Presumption of Innocent Principle, referring to the Criminal Procedure Code which is basically the principle of presumption of innocence narrowly interpreted how someone should be stated not guilty before a verdict / verdict is declared guilty. Second, barriers to the implementation of the protection of the rights of suspects in providing information freely in the process of investigating investigations in the Pekanbaru City Police Pekanbaru are, factors of law enforcement officials, cultural factors, community factors and factors of facilities and infrastructure problems. The author recommends: First, law enforcers, in this case Police Investigators, in conducting criminal case investigations of suspects in order to apply the Presumption of Innocent Principle and uphold human rights, because everyone must be considered innocent before there is a verdict the court which stated his guilt and had obtained permanent legal force. Second, the suspect in order to expedite the investigation process should provide honest and uncomplicated statements, so that the examination process can run smoothly and do not occur things that can cause violence against suspects and violations of human rights.Keywords: Suspect Rights, Principle of Presumption of Innocence, Investigation